(untitled) (Research, Society and Development, 2022)
The implementation of the National Oral Health Policy aimed to organize care networks in the Unified Health System. The investigation aims to evaluate the flow of dental services in the city of Fortaleza, Ceará, northeast of Brazil. This is a qualitative research, which used the Primary Health Care, Secondary (Center for Dental Specialties) and Tertiary Care. In the study, 04 managers and 09 dentists from the selected units participated. The collection of information, carried out during the year 2021, was extracted through an interview. The hermeneutic narrative was used to analyze the discourses, dividing them into: access to dental services, regulation of dental services and distribution of professionals in the network. It was found that the units have large territorial areas that generate geographic barriers to access the services offered. This is one of the factors that generate queues for procedures, causing significant absenteeism in the provision of services. It was also identified an insufficient number of professionals to meet the demand and failures in scheduling appointments. It was finished that it is necessary to create a standardized protocol for scheduling appointments in primary care, to expand the number of oral health professionals at this level of care and in dental specialty centers, and promote the implementation of new centers.